2019
DOI: 10.1108/hff-07-2018-0382
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study and POD snapshot analysis of flow characteristics for pulsating turbulent opposing jets

Abstract: Purpose The purpose of this study is to investigate the coherent structures of pulsed opposing jets by large eddy simulation (LES) model and proper orthogonal decomposition (POD) snapshot method. Flow pulsation as an active flow control method is considered for the enhancement of transport phenomena in impinging jets. The effect of flow pulsation parameters such as pulsation signal shape and frequency on the vortical coherent structures, the energy content of primary modes and their variation are studied numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Increased heat transfer by moderate flow pulsation has therefore been considered, as vibrational behavior anyway occurs in many practical applications (Bagheri et al , 2019; Rama Narasimha et al , 2010; Hoseinzadeh et al , 2019). Another method to enhance heat transfer is the use of nanofluids, which has been widely considered in recent years (Hoseinzadeh et al , 2017; Hoseinzadeh et al , 2018; Hoseinzadeh et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Increased heat transfer by moderate flow pulsation has therefore been considered, as vibrational behavior anyway occurs in many practical applications (Bagheri et al , 2019; Rama Narasimha et al , 2010; Hoseinzadeh et al , 2019). Another method to enhance heat transfer is the use of nanofluids, which has been widely considered in recent years (Hoseinzadeh et al , 2017; Hoseinzadeh et al , 2018; Hoseinzadeh et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They showed the dynamics of Kelvin-Helmholtz (K-H) vortices, counter-rotating vortex pair and hairpin vortices and the effect of these vortices on surface film cooling effectiveness. Bagheri et al (2019) studied the LES results of pulsating turbulent opposing jets using the POD method. They found that regular ring and twin vortices were created and induced strong velocity fluctuation.…”
Section: Introductionmentioning
confidence: 99%